2015
DOI: 10.1007/s13277-015-3781-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenylbutyrate—a pan-HDAC inhibitor—suppresses proliferation of glioblastoma LN-229 cell line

Abstract: Phenylbutyrate (PBA) is a histone deacetylase inhibitor known for inducing differentiation, cell cycle arrest, and apoptosis in various cancer cells. However, the effects of PBA seem to be very cell-type-specific and sometimes limited exclusively to a particular cell line. Here, we provided novel information concerning cellular effects of PBA in LN-229 and LN-18 glioblastoma cell lines which have not been previously evaluated in context of PBA exposure. We found that LN-18 cells were PBA-insensitive even at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 49 publications
(66 reference statements)
0
42
0
Order By: Relevance
“…An a posteriori study concluded that the pharmacokinetics and pharmacodynamics of PB in glioblastoma patients is affected by concomitant administration of P450-inducing anticonvulsants [52], it being plausible that the limited concentrations of PB achievable in the cells in vivo partly explain the lack of efficiency shown in the earlier clinical trials. In agreement with this, a very recent study has assessed PB-treatment in different glioblastoma cell lines, concluding that the effects of PB seem to be cell-type-specific in a dose-dependent manner [56]. …”
Section: Ammonia-scavenging Drugsmentioning
confidence: 60%
“…An a posteriori study concluded that the pharmacokinetics and pharmacodynamics of PB in glioblastoma patients is affected by concomitant administration of P450-inducing anticonvulsants [52], it being plausible that the limited concentrations of PB achievable in the cells in vivo partly explain the lack of efficiency shown in the earlier clinical trials. In agreement with this, a very recent study has assessed PB-treatment in different glioblastoma cell lines, concluding that the effects of PB seem to be cell-type-specific in a dose-dependent manner [56]. …”
Section: Ammonia-scavenging Drugsmentioning
confidence: 60%
“…Primer sequences for DDIT3 (CHOP), BAX, BCL2L11 (BIM), BCL2, BCL2L1 (BCL-X L ), PUMA, NOXA, and housekeeping RPL13A have been described in our previous work. 15,16 Sequences of the other PCR primers were previously described as: HSPA5 (GRP78), 22 SOD1, 23 SOD2, 23 CAT, 23 COX2, 24 and IL1B. 24 Additional evaluation of primer accuracy was done using Primer-BLAST software.…”
Section: Rna Isolation and Gene-expression Analysismentioning
confidence: 99%
“…A number of other factors, such as molecular heterogeneity, anaplastic cancer cells, and difficulties in targeting therapeutics specifically to transformed cells, are among the limitations halting development of effective glioblastoma therapies. [15][16][17] To address this need for new therapeutic strategies, the field of nanomedicine is currently being explored in the management of brain malignancies. 17 To date, several reports illustrating the utility of SiNPs for brain-tumor treatment have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the chaperoning activity of PBA may influence the ER stress/UPR activation, orchestrated by IRE1alpha (inositol-requiring enzyme 1 alpha), PERK (PKR-like endoplasmic reticulum kinase) and ATF6 (Cyclic AMP-dependent transcription factor ATF-6 alpha), which regulate the balance between cell survival and cell death, mainly based on the expression of BIP (Binding Immunoglobulin Protein) and CHOP (C/EBP Homologous Protein), respectively. Although PBA has been reported to induce apoptosis in the glioma cell line LN-2299 by downregulating the anti-apoptotic bcl2 family proteins [12] the underlying mechanisms have not been investigated. In this study, the impact of PBA treatment on mutant and wtp53 expression, on the mevalonate pathway and ER stress/UPR was addressed as possible mechanisms of cell death induction in U373, T98 and U87, glioblastoma cell lines harboring mutant and wtp53, respectively.…”
Section: Introductionmentioning
confidence: 99%